OPTIMALISASI ADOPSI INOVASI PROGRAM SIMOLEK PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PEKANBARU - Indri Islamiati; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Mobile Service Management Information System (SIMOLEK) Program is one of the forms of the development of technological advances in the governance that implements smart city. SIMOLEK is an innovation technology service that is adopted to be able to provide ease of service licensing and non-licensing online that is connected to the online central system single submission (OSS). The purpose of this research is to know how the process of adoption of SIMOLEK Technology program services and to know what are the supporting and aspirational factors in the process of adoption of such innovations. This research uses purposive sampling and the type of qualitative research with a descriptive approach and the data needed both primary and secondary data obtained by observation techniques, interviews and documentation for further analysis. The results of this research show that: first, the process of innovation of the program of Mobile Service Management Information System (SIMOLEK) in the Office of Investment and integrated service of one door Pekanbaru running is not optimal. Second, the supporting factor to adopt the innovation of SIMOLEK program, namely good leadership, and motivation. The inhibitory factor is very lacking socialization, community trusts, and half implemented Keywords: adoption innovation, service technology